Integrating legal english into pedagogical practices for future lawyers - Yatsyshyn, Nataliia (My University, 2024)
For law students, especially those who plan to practice international law, legal English is essential. There are particular difficulties for legal education because of the exacting character of legal language as well as formal structures and terminology. By incorporating Legal English into the legal curriculum, pedagogical approaches seek to prepare students for future professional situations by fostering their linguistic and legal competence. This study examines strategies for providing focused Legal English training to close the gap between language education and the practice of law.
Keywords: law; English; Legal English; lawyers